Nutritional Needs in Chronic Liver Disease - Zakirkhodjaev Sherzod Yaxyaevich; Jalolov Nozimjon Nodir o‘g‘li; Sadirova Mexriban Kuralbayevna; Niyazova Olga Andreevna; Abdirova Aygul Mamanovna (Genius Publishing Group, 2024)
In chronic liver diseases, nutritional status is often disturbed with the development of malnutrition of one degree or another. The use of nutritional support based on the nosological and syndromic approach makes it possible to create optimal conditions for the normalization of the function of the affected organ, increasing the effectiveness of other types of therapy and improving the prognosis of the disease.
Keywords: Chronic liver diseases; chronic hepatitis; diet therapy; nutrition